(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The technological and cultural development has brought about major political transformations and intellectual data and concepts that have changed the concepts of modernist thought, especially after the left movement to the maturation of new concepts that have the ability to respond to these changes, The most prominent of these are the deconstruction proposals that overthrew the center and celebrated the margin as the productive actor of the realities of life, which was confirmed by the concepts of postmodernism and cultural criticism, including the feminine body, which overthrew the masculine center. It turned from a marginal, hidden body to a life-oriented presence. For this reason, we found it important to monitor this conceptual transformation and active presence in it, and to discuss it in terms of the concept of stillness and invisibility to the act of creative manifestation and how to announce the categories of the body. For this reason, the research is divided into presenting the problematic of the concept and the importance of monitoring and the aim of this under the introduction tab, and then revealing this manifestation through the theoretical foundation that we divided into 1- The body is the conflict of the concept, 2- The philosophical position of the body, 3- Feminist criticism and manifestations of the body, 4- Results The conclusions and then the sources